TINJAUAN EKONOMI SYARIAH TERHADAP PELAKSANAAN BANTUAN MODAL SPP PNPM-MANDIRI (Simpan Pinjam Perempuan Program Nasional Pemberdayaan Masyarakat Mandiri) - Hidayatina Hidayatina; Desi Muliawati (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
The problem in this research is about the distribution of business capital aid with murabahah system for SPP PNPM-Mandiri in Gampong Murong Samudra District in the form of gold. The formulation of the problem in this research are: 1) how the implementation of the business capital assistance program for SPP PNPM-Mandiri in Gampong Murong Samudra Subdistrict) 2) how the sharia economy review on the implementation of capital assistance program for SPP PNPM-Mandiri in Gampong Murong Samudra subdistrict? is field research (field research) which to belong to qualitative research with the help of qualitative data. The results of this research are: 1) the implementation of business capital assistance for SPP PNPM-Mandiri in Gampng Murong Samudra sub-district using murabaha system in the form of gold in accordance with the amount in accordance with the granted by the UPK SPP PMPM- Mandiri management in Gampong Murong Samudra District . Then the gold is resold, for then the payment is made in installments. And benefits for UPK SPP PNPM is in the form of percentage of the loan amount of 1% every month 2) `Implementation of business capital assistance program SPP PNPM-Mandiri in Gampong Murong Samudra sub-district is not in accordance with Islamic economics, because the contract sale and purchase murabahah in sharia economy should mention the price of origin and profit must be agreed upon by both parties who berakad. And still from the values and principles of sharia economy.